Comparison of the Effects of Pelvic Compression Using Instruments on Trunk Muscle Endurance and Balance Ability in Subjects in Their Twenties With or Without Low Back Pain - Suh-young Chung; Suhn-yeop Kim (Physical Therapy Korea, 2022)
Background: Low back pain (LBP) is a representative disease, and LBP is characterized by muscle dysfunction that provides stability to the lumbar spine. This causes physical functional problems such as decreased posture control ability by reducing the muscular endurance and balance of the lumbar spine. Pelvic compression using instruments, which has been used dur-ing recent stabilization exercises, focuses on the anterior superior iliac spine of the pelvis and puts pressure on the sacroiliac joint during exercise, making the pelvis more symmetrical and stable. Currently, research has been actively conducted on the use of pelvic compression belts and non-elastic pelvic belts; however, few studies have conducted research on the application effect of pelvic compression using instruments.Objects: This study aimed to investigate whether there is a difference in trunk muscular en-durance and dynamic and static balance ability levels by applying pelvic stabilization through a pelvic compression device between the LBP group and the non-LBP group.Methods: Thirty-nine subjects currently enrolled in Daejeon University were divided into 20 subjects with LBP group and 19 subjects without LBP (NLBP group), and the groups were compared with and without pelvic compression. The trunk muscular endurance test was per-formed with 4 movements, the dynamic balance test was performed using a Y-balance test, and the static balance test was performed using a Wii balance board.Results: There was a significant difference the LBP group and the NLBP group after pelvic compression was applied to all tests (p < 0.05). In the static and dynamic balance ability test after pelvic compression was applied, there was a significant difference in the LBP group than in the NLBP group (p < 0.05).Conclusion: These results show that pelvic compression using instruments has a positive effect on both those with and without LBP and that it has a greater impact on balance ability when applied to those with LBP.